Properties advanced of the silicon nitride based ceramics and recent performance on automotive parts manufacture by machining process: Advanced Ceramics, demand Forecast - De Souza, José Vitor Candido; De Andrade Nono, Maria Do Carmo; Mineiro, Sergio Luiz; De MacEdo Silva, Olivério Moreira; Ribeiro, Marcos Valério [UNESP] (SAE International, 2008)
Automotive parts manufacture by machining process using silicon nitride-based ceramic tool development in Brazil already is a reality. Si 3N4-based ceramic cutting tools offer a high productivity due to their excellent hot hardness, which allows high cutting speeds. Under such conditions the cutting tool must be resistant to a combination of mechanical, thermal and chemical attacks. Silicon nitride based ceramic materials constitute a mature technology with a very broad base of current and potential applications. The best opportunities for Si3N 4-based ceramics include ballistic armor, composite automotive brakes, diesel particulate filters, joint replacement products and others. The goal of this work was to show latter advance in silicon nitride manufacture and its recent evolution on machining process of gray cast iron, compacted graphite iron and Ti-6Al-4V. Materials characterization and machining tests were analyzed by X-Ray Diffraction, Scanning Electron Microscopy, Vickers hardness and toughness fracture and technical norm. In recent works the authors has been proved to advance in microstructural, mechanical and physic properties control. These facts prove that silicon nitride-based ceramic has enough resistance to withstand the impacts inherent to the machining of gray cast iron (CI), compacted graphite iron (CGI) and Ti-6Al-4V (6-4). Copyright © 2008 SAE International.
Keywords: Advanced Ceramics; Automotive brake; Automotive parts; Ballistic armors; Compacted graphite iron; Cutting speed; Demand forecast; Diesel particulate filters; Gray cast iron; High productivity; Hot hardness; Joint replacement; Machining Process; Machining test; Materials characterization; Micro-structural; Potential applications; Recent performance; Silicon nitride-based ceramics; Technical norms; Ti-6al-4v; Tool development; Aluminum; Ceramic cutting tools; Fracture toughness; Friction materials; Graphite; Joint prostheses; Machining; Machining centers; Manufacture; Mechanical properties; Scanning electron microscopy; Silicon; Silicon nitride; X ray diffraction; Ceramic materials